What are the risks of oral contraceptives in females with migraines?. Issue 7 (July 2017) - Fortson, Chris; Mattam, Lisa; Zabakolas, George
Abstract : EVIDENCE‐BASED ANSWER : Oral contraceptive use in women with migraines is associated with a 7‐ to 8‐fold greater risk of ischemic stroke compared with women without migraines not using oral contraceptives (SOR: B, meta‐analysis of observational studies).